Factors affecting visual electronic word of mouth credibility on online purchase intention - Khan, Shamim Ahmed (2019)
Electronic word-of-mouth (eWOM) is an important tool for getting useful information about a product or service. eWOM can appear in different forms like text-based, visual-based, mixture of text and visual etc. One of the important issues regarding eWOM that needs addressing from researchers is the credibility of eWOM. There are several aspects of an eWOM message that can have impact on its credibility. Although source and message content are considered the most widely used determinants of eWOM credibility, certain other aspects also need to be taken into consideration such as receiver factor and vehicle factor. Using the Uncertainty Reduction Theory (URT), the present study assessed the impact of source credibility, argument quality, confirmation with prior belief of receiver, receiver susceptibility to interpersonal influence and platform reputation on the credibility assessment of visual eWOM. Moreover, the study also investigated the impact of visual eWOM credibility on online purchase intention among Malaysian consumers. Using quantitative research design, data for the present study was collected from 384 samples with a structured survey questionnaire. Combination of online and personally administered paper-based survey was used to collect the data. Active users of internet having familiarity with online reviews were selected as the sample of the study. Relevant analyses were done by applying structural equation modelling (SEM) technique using AMOS. Results indicate that source of the eWOM and platform reputation of eWOM have significant impact on credibility assessment of visual eWOM. Moreover, further analysis also reveals that visual eWOM credibility has significant positive impact on online purchase intention. The results imply that individuals in Malaysia put greater importance on the credibility of the person giving the visual-based eWOM. Moreover, visual eWOM available on reputed websites are perceived as credible by the receivers. Finally, visual eWOM found on social media platforms can motivate Malaysian consumers in developing online purchase intention. Therefore, while making any marketing strategy related to visual eWOM and online purchase, marketing practitioners in Malaysia should take the result of this study into consideration.